Remote versus in-office monitoring for implantable cardioverter defibrillators: results from a randomized pragmatic controlled study in Portugal - Oliveira, Mário (2022)
© 2022 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. This is an open access article under the CCBY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)